BANKS AND INTERNATIONAL TRADE FINANCE: GREEN PRACTICES IN LETTERS OF CREDIT - CLAUDIA GABRIELA BAICU (Global Economic Observer)
The aim of this paper is to assess the role of banks in green trade finance, with a focus on the letters of credit. The research findings highlight that, among other initiatives, banks have begun to promote sustainable development through trade finance products, facilitating international trade in environmental goods and services. The multilateral development banks can also contribute to increasing international trade finance availability. In this respect, the trade finance facilitation programmes developed by the International Finance Corporation and the European Bank for Reconstruction and Development are relevant. However, green trade finance is facing a lot of challenges, including lack of international standards, but efforts are underway to address them.